Optimalisasi Daya Saing UMKM Jeje Jangek Melalui Literasi Keuangan Digital di Desa Tanjung Gusta - Nurly Aulia Rahman; Irwilda Mahliza Nst; Rahimah Rahimah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Implementation of Real Work Lectures is one manifestation of the Tri Dharma of Higher Education, namely empowerment and community service. On this occasion the author carried out Real Work Lecture activities in Tanjung Gusta Village with the main program headline being the socialization of financial literacy to micro, small and medium business actors, especially fish cracker or jangek cracker business actors. The approach used consists of three methods, namely observation, interviews and documentation. The main work program implemented was visiting business actors making skin crackers to socialize about financial literacy and digital promotion. Then the author also held two supporting work programs, namely the socialization of financial literacy education and sharia investment, the main focus of which was on education about investment and financial management and the second was the implementation economic market day for elementary school students with the aim of cultivating students' talents and interests in the field of entrepreneurship. Both the main and supporting work programs were carried out well and without significant obstacles due to support from Tanjung Gusta Village officials, the community and fellow students who worked together to make the work program successful.